Бібліотека ЗВО: місце та роль в освітньому процесі - Біла, Валерія Костянтинівна; Byla, Valeriya (ЦНТУ, 2025)
У дослідженні представлено чітке розуміння основних проблем бібліотечної діяльності, таких як обмежене фінансування, недостатність кадрової бази та необхідність постійного оновлення бібліотечних ресурсів. Разом з тим автор також визначає перспективи розвитку бібілотечної сфери ЗВО, що пов'язані з інноваціями, цифровізацією та інтеграцією новітніх технологій в роботу бібліотек. The study presents a clear understanding of the main problems of library activities, such as limited funding, insufficient human resources and the need for constant updating of library resources. At the same time, the author also identifies the prospects for the development of the library sector of higher education institutions, which are associated with innovation, digitalization and integration of the latest technologies into the work of libraries.
University Library: Place and Role in the Educational Process
Keywords: бібліотека; заклад вищої освіти; бібліотечний фонд; електронні ресурси; цифрові технології; library; higher education institution; library fund; electronic resources; digital technologies